Mine, Mine, Mine: Self-Reference and Children’s Retention of Novel Words - Axelsson, Emma L.; Dawson, Rachelle L.; Yim, Sharon Y.; Quddus, Tashfia (Frontiers in Psychology, 2018)
Adults demonstrate enhanced memory for words encoded as belonging to themselves compared to those belonging to another. Known as the self-reference effect, there is evidence for the effect in children as young as three. Toddlers are efficient in linking novel words to novel objects, but have difficulties retaining multiple word-object associations. The aim here was to investigate the self-reference ownership paradigm on 3-year-old children’s retention of novel words. Following exposure to each of four novel word-object pairings, children were told that objects either belonged to them or another character. Children demonstrated significantly higher immediate retention of self-referenced compared to other-referenced items. Retention was also tested four hours later and the following morning. Retention for self- and other-referenced words was significantly higher than chance at both delayed time points, but the difference between the self- and other-referenced words was no longer significant. The findings suggest that when it comes to toddlers’ retention of multiple novel words there is an initial memory enhancing effect for self- compared to other-referenced items, but the difference diminishes over time. Children’s looking times during the self-reference presentations were positively associated with retention of self-referenced words four hours later. Looking times during the other-reference presentations were positively associated with proportional looking at other-referenced items during immediate retention testing. The findings have implications for children’s memory for novel words and future studies could test children’s explicit memories for the ownership manipulation itself and whether the effect is superior to other forms of memory supports such as ostensive naming.